Therapeutic Silencing of Bcl-2 by Systemically Administered siRNA Nanotherapeutics Inhibits Tumor Growth by Autophagy and Apoptosis and Enhances the Efficacy of Chemotherapy in Orthotopic Xenograft Models of ER (−) and ER (+) Breast Cancer - Ibrahim Tekedereli; S Neslihan Alpay; Ugur Akar; Erkan Yuca; Cristian Ayugo-Rodriguez; He-Dong Han; Anil K Sood; Gabriel Lopez-Berestein; Bulent Ozpolat (Elsevier, 2013)
Bcl-2 is overexpressed in about a half of human cancers and 50-70% of breast cancer patients, thereby conferring resistance to conventional therapies and making it an excellent therapeutic target. Small interfering RNA (siRNA) offers novel and powerful tools for specific gene silencing and molecularly targeted therapy. Here, we show that therapeutic silencing of Bcl-2 by systemically administered nanoliposomal (NL)-Bcl-2 siRNA (0.15 mg siRNA/kg, intravenous) twice a week leads to significant antitumor activity and suppression of growth in both estrogen receptor-negative (ER(−)) MDA-MB-231 and ER-positive (+) MCF7 breast tumors in orthotopic xenograft models (P < 0.05). A single intravenous injection of NL-Bcl-2-siRNA provided robust and persistent silencing of the target gene expression in xenograft tumors. NL-Bcl-2-siRNA treatment significantly increased the efficacy of chemotherapy when combined with doxorubicin in both MDA-MB-231 and MCF-7 animal models (P < 0.05). NL-Bcl-2-siRNA treatment-induced apoptosis and autophagic cell death, and inhibited cyclin D1, HIF1α and Src/Fak signaling in tumors. In conclusion, our data provide the first evidence that in vivo therapeutic targeting Bcl-2 by systemically administered nanoliposomal-siRNA significantly inhibits growth of both ER(−) and ER(+) breast tumors and enhances the efficacy of chemotherapy, suggesting that therapeutic silencing of Bcl-2 by siRNA is a viable approach in breast cancers.